Wszczęcie i data zakończenia postępowania w przedmiocie wykonania kary ograniczenia wolności - Kalisz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The paper focuses on the problems associated with the instigation and closure of enforcement proceedings concerning restriction of liberty. In the case of restriction of liberty, the moments in question are regulated by several separate provisions: Article 57a of the Criminal Enforcement Code, Article 64 of the Criminal Enforcement Code and Article 83 of the Criminal Code. The starting date of the restriction of liberty sentence period is by no means obvious and leads to very individual problems. Precise indication of this date is crucial to the determination of the date of the end of the sentence period as well as legal consequences associated with this date.
Keywords: ograniczenie wolności; skrócenie kary; okres wykonania kary